Analysis of Governor's Regulation Concerning the Implementation of Large-Scale Social Restrictions in Handling Covid-19 - Ahmad Kahar Maranjaya; Rifani Firyal Faruqi (Eduvest - Journal of Universal Studies, 2021)
The purpose of the issuance of this Government Regulation concerning Large-Scale Social Restrictions is to ensure that the Regional Government does not take individual steps, so that with the existence of this Government Regulation, steps handling of Covid 19 can be in line with the Central Government. For this reason, the author is interested in conducting research with the aim of finding out whether Pergub Number 88/2020 is the implementing regulation of the legislation. This study uses a normative juridical approach. In conducting the research, the writer uses the library research method to review a statutory regulation, which can be obtained from a literature research by using primary, secondary, and tersier legal materials. Based on the discussion of this research, it is concluded that the Governor's Regulation Number 88 of 2020 concerning the Implementation of Large-Scale Social Restrictions (PSBB) in Handling Corona Virus Disease 2019 (Covid-19) which was issued first before the regional regulations that were formed later needed to be updated in substance into a Regional Regulation and issued back to the new Governor Regulation. This step is taken to ensure the synchronization of the national legal system by means of vertical synchronization and horizontal synchronization. In Government Regulation No. 38 of 2007 which is a derivative of Law no. 32 of 2004 regulates the division of government affairs between the Government, Province, and Regency/City.